Multi-Party Governance of Older Adult Care and Implications for Gerontological Social Work in Central China - Li, Peng; Suttawet, Chokchai (Journal of Population and Social Studies [JPSS], 2026)
This study investigates how multi-party governance operates in older adult care systems in Central China and its implications for gerontological social work. Drawing on 50 semi-structured interviews with stakeholders across government, social organizations, communities, market actors, volunteers, and families in Hubei Province, the study employs NVivo-assisted thematic analysis to examine governance processes, actor roles, and service delivery patterns. Findings indicate that while diversified participation has expanded community- and home-based care, governance remains uneven across urban and rural contexts. Key constraints include funding instability, workforce shortages, limited professionalization, and asymmetric power relations between government and non-state actors. Social organizations function as intermediaries linking policy and practice but operate with limited autonomy due to dependence on government procurement. Social workers are increasingly called upon to navigate fragmented care networks as connectors between policy frameworks and grassroots practice. The study concludes that sustainable governance requires stronger institutional support, clearer role delineation, and enhanced professional training, with implications for social work education and aging policy.